Correlation of Plasma Melatonin Concentration and Alertness Level Among Female Nurses in Jakarta Indonesia - Kresna, Andreas; Fuk, Liem Jen; Widyahening, Indah Suci; Soemarko, Dewi Sumaryani; Fitriani, Dewi Yunia (UI Scholars Hub, 2023)
Background Working in shift especially night shift could alter alertness level, increase fatigue, and working accident. One of the factors that affect the circadian rhythm were melatonin. Melatonin was a hormone that regulate the wake and sleep cycle that have an impact on alertness levels. This study was aimed to find correlation between plasma melatonin and alertness level. Methods A cross-sectional study was conducted on 40 female night shift nurses. Individual characteristics were obtained by self-administered questionnaire. Plasma melatonin concentrations and alertness level was collected twice at night time (11 pm – 00 am) and at morning (7 am − 8 am). Spearman or Pearson test was used to find correlation between melatonin concentrations and Psychomotor Vigilance Test (PVT). Results Mean age was 28.4 (±4.9) years with working experience varied from 1-16 years. Plasma melatonin concentrations among female night shift nurses were higher before working hours than after duty. Range of plasma melatonin value was 10-240 pg/ml and Alertness was in the same manner with average alertness level at night was 301.2 ± 51.6 ms and 293.2± 49.7 ms at morning. There was a weak correlation between plasma melatonin concentration and alertness level difference before and after duty (r = 0.37; p = 0.016). Conclusion There was weak correlation between plasma melatonin and alertness level in night shift workers before and after duty. To Maintain alertness level reduction and melatonin secretion, night shift workers should rest at least 30 minutes during their working hours, always keep the lights on while on duty and should not work more than one shift on the same day, and providing healthy foods.